Attitude Of Employed Mothers and Housewives Toward Family Physicians in Primary Health Care Centers - Salih Ismael, Nibras; Hussein Kadhim, Shahad (South Asian Journal of Social Sciences and Humanities, 2025)
Aim of study: To evaluate the attitude of Employed mothers and housewives toward family physicians in primary health centers and to identify the general satisfaction of participants with the services provided by Family physicians. Method: A cross-sectional study was conducted in 4 primary health care centers in Baghdad (AL-Resafah sector, AL-Karikh sector), period from 1st of January 2019 to 1st of June 2019. Sample of a study from a mother who attending the PHCC who have multiple visits, information was obtained by interviewing participants and data entry and analysis was done by using (SPSS-24) then categorized into tables and figures. Result: A total of 250 participants included in this study, the most common age groups was 25-45 years. 62% were married and the rest were either widow or divorced. 72.8% were living in urban area and the rest 27.2% were from rural area. Nearly half of participants were Employed, 112(44.8%) of participants they prefer physicians’ age≥45y, 128(51.2%) of participants they have no difference for preferring physicians’ gender. Conclusion: More than half of participants have good attitude toward family physician. There was no statistically significant difference with some of participants’ characteristics and satisfaction level. Some of participants showed dissatisfaction with the appointment for the next visit and more than half showed dissatisfaction with the waiting time.